HTLV-1 proviral load in infective dermatitis associated with HTLV-1 does not increase after the development of HTLV-1-associated myelopathy/tropical spastic paraparesis and does not decrease after IDH remission. - Everton S Batista; Pedro D Oliveira; Janeusa Primo; Cinthya Maria Neves Varandas; Ana Paula Nunes; Achiléa L Bittencourt; Lourdes Farre (Public Library of Science (PLoS), 2019)
Introduction Infective dermatitis associated with HTLV-1 (IDH) is a recurrent eczema which affects children vertically infected with HTLV-1. In Bahia, Brazil, we recently reported that 47% of IDH patients also develop juvenile HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), a progressive disabling disorder which is typically reported in adult HTLV-1 carriers. IDH may also predispose to adult T-cell leukemia/lymphoma, a neoplasm associated with HTLV-1. The factors relating to the development of HTLV-1-associated juvenile diseases have not yet been defined. HTLV-1 proviral load (PVL) is one of the main parameters related to the development of HTLV-1 associated diseases in adults. In the current study, we investigated the role of PVL in IDH and juvenile HAM/TSP. Methodology/principal findings This is a cohort study that included fifty-nine HTLV-1 infected children and adolescents, comprising 16 asymptomatic carriers, 18 IDH patients, 20 patients with IDH and HAM/TSP (IDH/HAM/TSP) and five with HAM/TSP. These patients were followed-up for up to 14 years (median of 8 years). We found that PVL in IDH and IDH/HAM/TSP patients were similarly higher than PVL in juvenile asymptomatic carriers (p<0.0001). In those IDH patients who developed HAM/TSP during follow-up, PVL levels did not vary significantly. HAM/TSP development did not occur in those IDH patients who presented high levels of PVL. IDH remission was associated with an increase of PVL. Inter-individual differences in PVL were observed within all groups. However, intra-individual PVL did not fluctuate significantly during follow-up. Conclusions/significance High PVL in IDH patients was not necessary indicative of progression to HAM/TSP. PVL did not decrease after IDH remission. The maintenance of high PVL after remission could favor early development of ATL. Therefore, IDH patients would have to be followed-up even after remission of IDH and for a long period of time.